2021
DOI: 10.3390/cells11010052
|View full text |Cite
|
Sign up to set email alerts
|

Cysteamine with In Vitro Antiviral Activity and Immunomodulatory Effects Has the Potential to Be a Repurposing Drug Candidate for COVID-19 Therapy

Abstract: The ongoing pandemic of coronavirus disease-2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), needs better treatment options both at antiviral and anti-inflammatory levels. It has been demonstrated that the aminothiol cysteamine, an already human applied drug, and its disulfide product of oxidation, cystamine, have anti-infective properties targeting viruses, bacteria, and parasites. To determine whether these compounds exert antiviral effects against SARS-CoV-2, we used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 46 publications
2
18
0
Order By: Relevance
“…Recently, we have reported that cysteamine and its oxidation product cystamine exert a direct antiviral action against the Wild type SARS-CoV-2 strain isolated at INMI L. Spallanzani IRCCS [ 15 ]. We then tested whether cysteamine had an impact on the life cycle of recent SARS-CoV-2 VOC and, therefore, we performed the viral-induced cytopathic effects (CPE) inhibition assay in Vero E6 cells.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we have reported that cysteamine and its oxidation product cystamine exert a direct antiviral action against the Wild type SARS-CoV-2 strain isolated at INMI L. Spallanzani IRCCS [ 15 ]. We then tested whether cysteamine had an impact on the life cycle of recent SARS-CoV-2 VOC and, therefore, we performed the viral-induced cytopathic effects (CPE) inhibition assay in Vero E6 cells.…”
Section: Resultsmentioning
confidence: 99%
“…To understand whether cysteamine directly affects the life cycle of the different SARS-CoV-2 variants, we measured the amount of the infectious viral particles released in the culture medium of Vero E6 cells treated with either cysteamine or with the drug-vehicle (H 2 O) at 72 h.p.i. We evaluated viral production by back-titrating the culture supernatants of the infected cells using a limiting dilution assay, as we recently described [ 15 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cysteamine and cystamine significantly decreased the viral production in Vero E6 and Calu-3 cells, and their antiviral action did not depend on the treatment time with respect to SARS-CoV-2 infection. Additionally, they showed an anti-inflammatory effect by lowering the SARS-CoV-2 specific IFN-γ production in vitro, using blood samples from COVID-19 patients [ 146 ].…”
Section: Recent Preclinical Studiesmentioning
confidence: 99%
“…Moreover, recently it has been shown that cysteamine is also capable of inhibiting infectivity of SARS-CoV-2 presumably by inhibiting the binding of S1 protein to ACE-2 receptor (14). Cysteamine and its disulfide cystamine also display an anti-inflammatory effect, reducing SARS-CoV-2 specific interferon-gamma production (15). In this report we examine the inhibitory activity of cysteamine in vitro against major variants of SARS-CoV-2 that have emerged so far and find that cysteamine inhibits them at achievable concentrations less than that currently approved by USFDA for ophthalmic use.…”
Section: Introductionmentioning
confidence: 99%